EMPLOYEE COMMITMENT INCREASE IN VIEWED FROM SOCIALIZATION OF STANDARD SANITATION OPERATIONAL PROCEDURE (SSOP) IN FOOD INDUSTRY COMPANIES (Case Study at PT Yummy Food Utama, Jakarta) - Dwi Rorin Mauludin Insana; Ria Susanti Johan (MBA - Journal of Management and Business Aplication, 2020)
Thisstudy aims to determine whether there is an influence between the socialization of Standard Sanitation Operational Procedures with employee work commitments in food industry companies (Case study at PT. Yummy Food Utama, Jakarta). The method used in this study is a survey method with associative techniques. Data collection was carried out by distributing questionnaires to 30 respondents to find out respondents' perceptions, understanding and satisfaction with the socialization of SSOP, as well as questionnaires for employee commitment in implementing SSOP. Based on the results of calculations and data analysis and discussions that have been carried out, it can be concluded that the socialization of the Standard Sanitation Operational Procedure has a positive and significant relationship with employee work commitments at PT. Yummy Food Utama, Jakarta.Keywords:Standard Sanitation Operational Procedure, Work commitment Keywords:Standard Sanitation Operational Procedure, Work commitment